Simulation study on the quenching characteristics of molten steel slag under different quenching media and modes - Jiahao Zhang; Jingcai Chang; Qinglei Liu; Zongqiang Li; Taiyang Liu; Chunyan Xu; Peng Wang; Hongfei Wu (Case Studies in Thermal Engineering)
China's water-quenched steel slag is largely landfilled due to low utilization, and slag gas quenching, despite being eco-friendly and water-efficient, faces challenges such as high energy consumption, low value-added output, along with safety risks arising from thermal and compositional limitations, it is therefore imperative to develop advanced quenching media and processes. To address this, this study proposes a convenient, cost-effective quenching method utilizing CO2-rich gas and slag as raw materials. Results show that the complete solidification time in the new mixture medium is nearly halved compared to that in the air medium. Furthermore, the two mediums exhibit distinct solid-liquid interface dynamics: in air, the slag's interface propagates inward from the exterior, whereas bidirectional propagation occurs simultaneously at a significantly faster rate in the new medium. In quenching features sense, a faster cooling rate and a hundred milliseconds duration effectively inhibit the decomposition of C3S and β-C2S to γ-C2S phase change. In ensuring security sense, the time required for the semi-solidification of new mixture media with a gas temperature of 1000 K is less than that for air with a temperature of 400 K. In the carbon fixation sense, the CO2-rich gas quenching process promotes reaction kinetics of carbonation and has a positive effect on eliminating remaining f-CaO and f-MgO. This approach has great potential to scale up, and points out the direction for sustainably converting waste steel slag into high-quality active admixture combined with substantial heat recovery.